Odpowiedzi

Najlepsza Odpowiedź!
2010-02-09T13:10:52+01:00
A1 = 3x+15,
a2=12,
a3= 27x-1
an=a1+(n-1)*r

a2=a1+(2-1)*r
a3= a1+ (3-1)*r

12 = 3x+15 + r
27x-1= 3x+15 +2r

r = -3x-3
24x-16 =2r /:2

r = -3x-3
r = 12x-8

-3x-3 = 12x - 8
-15x = -5
x = 1/3

2010-02-09T13:14:06+01:00
Korzystamy z tego, że:
a₂=a₁+r
a₃=a₁+2r
a₄=a₁+3r
itd.

więc u nas:
a₃=a₁+2r

12=3x+15+2r
-3=3x+2r

oraz:
a₅=a₁+4r
27x-1=3x+15+4r
24x-16=4r |:4
6x-4=r
r=6x-4

skoro już wiemy, że r=6x-4 to wstawiamy to pod równanie:
-3=3x+2r
-3=3x+2(6x-4)
-3=15x-8
5=15x |:15
x=⅓